2019
DOI: 10.5964/psyct.v12i1.275
|View full text |Cite
|
Sign up to set email alerts
|

Survey on Om meditation: Its effects on the human body and Om meditation as a tool for stress management

Abstract: Meditation and yoga both have positive effects on physical, as well as mental health. Om mantra chanting, a simple and easy to practice, also comes under the aspect of meditation. The “Om” mantra is also considered as the very name of the absolute. Om meditation not only affects the various parts of the brain, such as pre-frontal cortex, vagus nerve, amygdala and others but also affects the heart rate and respiratory rate. Considering the healing effects of Om meditation, through this paper, we are trying to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…To date, only a few studies have investigated the effects of meditation techniques that are less well known but still very important and prevalent in their specific traditions. These techniques include visualization (Amihai & Kozhevnikov, 2014;Lou et al, 1999), nondual awareness (Josipovic, 2010), supine/ relaxation meditation (Gul & Jahangir, 2019;Kjaer et al, 2002), chanting (Harne et al, 2019;Wolf & Abell, 2003), analytical meditation (van Vugt et al, 2020), contemplation (Bach & Guse, 2015), energy meditation (Venkatesh et al, 1997), dynamic meditation (Bansal et al, 2016), or whirling meditation (Cakmak et al, 2017).…”
mentioning
confidence: 99%
“…To date, only a few studies have investigated the effects of meditation techniques that are less well known but still very important and prevalent in their specific traditions. These techniques include visualization (Amihai & Kozhevnikov, 2014;Lou et al, 1999), nondual awareness (Josipovic, 2010), supine/ relaxation meditation (Gul & Jahangir, 2019;Kjaer et al, 2002), chanting (Harne et al, 2019;Wolf & Abell, 2003), analytical meditation (van Vugt et al, 2020), contemplation (Bach & Guse, 2015), energy meditation (Venkatesh et al, 1997), dynamic meditation (Bansal et al, 2016), or whirling meditation (Cakmak et al, 2017).…”
mentioning
confidence: 99%
“…Om chanting is a powerful means of purifying, strengthening, and awakening the elements of human being (Saraswati & Stevenson, 2017). It stabilizes the brain, keeps the mind steady, refreshes all the seven energy centers (i.e., root, sacral, throat, heart, third eye, crown, and the higher octave of the root) (Gurjar & Ladhake, 2016), and reduces stress and anxiety (Gurjar & Ladhake, 2016; Harne et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…[ 5 ] Chanting of OM reduces anxiety and depression, facilitating better states of relaxation conducive to improved mental and physical health. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…Although OM has been used in spirituality for centuries, scientific research with quantifiable physical measures started to expand in the 1990s when laboratories explored the effects of OM meditation on human beings by investigating various parameters such as electroencephalograph, neuroimaging, evoked potentials, and other methods. [ 6 7 8 ] These studies have suggested that chanting OM could produce numerous physiological changes such as increased awareness, sensitivity to sensory transmission, improved concentration, reduced stress levels, heart rate, blood pressure, and skin resistance. [ 3 9 10 11 ]…”
Section: Introductionmentioning
confidence: 99%